PML regulates apoptosis at endoplasmic reticulum by modulating calcium release - Giorgi, Carlotta; Ito, Keisuke; Lin, Hui-Kuan; Santangelo, Clara; Wieckowski, Mariusz R; Lebiedzinska, Magdalena; Bononi, Angela; Bonora, Massimo; Duszynski, Jerzy; Bernardi, Rosa; Rizzuto, Rosario; Tacchetti, Carlo; et al. (Science (American Association for the Advancement of Science), 2010)
The promyelocytic leukemia (PML) tumor suppressor is a pleiotropic modulator of apoptosis. However, the molecular basis for such a diverse proapoptotic role is currently unknown. We show that extranuclear Pml was specifically enriched at the endoplasmic reticulum (ER) and at the mitochondria-associated membranes, signaling domains involved in ER-to-mitochondria calcium ion (Ca(2+)) transport and in induction of apoptosis. We found Pml in complexes of large molecular size with the inositol 1,4,5-trisphosphate receptor (IP(3)R), protein kinase Akt, and protein phosphatase 2a (PP2a). Pml was essential for Akt- and PP2a-dependent modulation of IP(3)R phosphorylation and in turn for IP(3)R-mediated Ca(2+) release from ER. Our findings provide a mechanistic explanation for the pleiotropic role of Pml in apoptosis and identify a pharmacological target for the modulation of Ca(2+) signals.